Comparative study on effect of various induction methods on sputum smear positivity (Bangladesh Journal of Medical Science, 2017)
Introduction: Under RNTCP, the diagnosis of 25-30% tuberculosis cases with negative bacteriological report with radiographic evidence and with smear negativity due to inability to expectorate adequate amount of sputum are left untreated which ultimately increases the burden of tuberculosis. Such cases can be subjected to induction methods to improve yield of positive result in sputum.Methodology: Study was undertaken on all 538 patients who attended the Chest and Tuberculosis department in DOTS Microscopy centre of HIMS. Intervention was done only in those found smear negative but clinically and radiologically suggestive of pulmonary tuberculosis who gave written consent i.e. = 92 subjects (Chest Physiotherapy (N=92); Nebulization (N=92) & Broncho-alveolar lavage (N=14).Results: Out 362 (67%) eligible subjects 228 were sputum negative, 92 patients gave consent for induction were subjected to chest physiotherapy for sputum induction of which 38 (41.3%) subjects came out to be sputum positive. Out of 92 patients subjected to nebulization for sputum induction 40 (43.4%) subjects yield sputum positive result. 14 patients were subjected to BAL (bronchoalveolar lavage) method to collect sputum sample of which 7(50%) came out to be sputum positive. (p=0.02).Conclusion: The non-invasive and cost effective methods of sputum induction should be incorporated more commonly in national programme as they provide better yield of sputum positivity.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.397-400